Identification of the Active Ingredient and Beneficial Effects of Vitex rotundifolia Fruits on Menopausal Symptoms in Ovariectomized Rats - Ji Hwan Lee; Sullim Lee; Quynh Nhu Nguyen; Hung Manh Phung; Myoung-Sook Shin; Jae-Yong Kim; Hyukjae Choi; Sang Hee Shim; Ki Sung Kang (Biomolecules, 2021)
Estrogen replacement therapy is a treatment to relieve the symptoms of menopause. Many studies suggest that natural bioactive ingredients from plants resemble estrogen in structure and biological functions and can relieve symptoms of menopause. The fruit of V. rotundifolia, called “Man HyungJa” in Korean, is a traditional medicine used to treat headache, migraine, eye pain, neuralgia, and premenstrual syndrome in Korea and China. The aim of the present study was to confirm that V. rotundifolia fruit extract (VFE) exerts biological functions similar to those of estrogen in menopausal syndrome. We investigated its in vitro effects on MCF-7 cells and in vivo estrogen-like effects on weight gain and uterine contraction in ovariectomized rats. Using the polar extract, the active constituents of VFE (artemetin, vitexicarpin, hesperidin, luteolin, vitexin, and vanillic acid) with estrogen-like activity were identified in MCF-7 cells. In animal experiments, the efficacy of VFE in ameliorating body weight gain was similar to that of estrogen, as evidenced from improvements in uterine atrophy. Vitexin and vitexicarpin are suggested as the active constituents of V. rotundifolia fruits.